ANALISIS PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA, AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA KEUANGAN DAERAH KOTA MALANG - Esni, Maria Trimurni; Made, Anwar; Wulandari, Retno (Jurnal Riset Mahasiswa Akuntansi, 2019)
Regional Autonomy is the right, authority and obligation of autonomous regions to regulate and manage their own government affairs and the interests of local communities in accordance with statutory regulations. The basic consideration of the implementation of regional autonomy is the development of conditions in the country that indicate that the rise of globalization that demands competitiveness of each country, including the competitiveness of local governments. This study aims to determine and analyze the effect of the implementation of performance-based budgeting, accountability and transparency as an independent variable both partially and simultaneously on the financial performance of the city of Malang. This study uses a quantitative approach with a sample of 44 employees in OPD and BPKAD Malang. Measurement of variables using a Likert Scale with a score of up to 5. Data were analyzed using multiple linear regression analysis and to test the significance level using the f test and hypothesis testing using t test with the help of the SPSS 22 program. Partial results indicate that the application of performance-based budgeting has a significant effect on regional financial performance, the accountability variable has a significant effect on regional financial performance and the transparency variable does not affect the regional financial performance and the results of research simultaneously show that the application of performance-based budgeting, accountability and transparency affects the regional financial performance